Unraveling Tragia peltata (Euphorbiaceae): taxonomy, morphology, distribution and conservation - Freire De Sá Cordeiro, Wesley Patrício; de Melo, André Laurênio; Ferreira De Sales, Margareth; Athiê-Souza, Sarah Maria (Phytotaxa, 2022)
Tragia peltata was published by Friar José Mariano da Conceição Vellozo in 1831, with a brief description of the leaf blade and a rudimentary illustration, subsequently Müller Argoviensis measured the size leaf blade—those being the only references to this species for more than 190 years. Specimens collected from 1971 onwards from the Brazilian states of Bahia, Espírito Santo, and Rio de Janeiro were recently encountered, however, in herbaria in that country. It is therefore possible to complement the description of T. peltata, update its geographic distribution range, and determine its conservation status; the species is also lectotypified here.